Sport and the American occupation of the Philippines bats, balls, and bayonets - Gems, Gerald R. (Lexington Books, 2016)
This interdisciplinary study analyzes the role of sport during the American occupation of the Philippines and how it related to race, religion, government, and more. It examines how sport was used by colonial authorities to achieve occupation aims and argues that similar strategies continue to be prominent factors in U.S. foreign policy.